Relation between E2 transitions in even–even and odd-mass nuclei - Van Isacker Piet (EPJ Web of Conferences, 2025)
How is the B(E2; 2+1 → 0+1) value in an even-even nucleus related to corresponding B(E2; Ji → Jf) values in a neighbouring odd-mass nucleus? If either neutrons or protons are confined to a single- j orbital and if the nucleon-nucleon interaction conserves seniority, a simple relation between the two properties is obtained, which may differ from what is found in the weak-coupling limit of the core-particle model. This single-j relation is substantially perturbed if several non-degenerate orbitals are considered. An application to recently measured B(E2) values in neutron-deficient tin isotopes is presented.